The Effectiveness of Emotion-Focused Therapy on Psychological Security in Women Involved in Domestic Violence - Tahereh Yarmohammadi; Saeed Teymouri; Alireza Rajaei (Iranian Journal of Educational Research)
Objective: The present investigation aimed to examine the efficacy of emotion-focused therapy in relation to the perception of psychological security and its components in women affected by domestic violence. Methods: The research employed a quasi-experimental design with a pre-test-post-test arrangement, incorporating a control group. The target population consisted of all women impacted by domestic violence who sought assistance from the forensic medicine department in the city of Kashmar during the first half of 2022. A total of 40 women experiencing domestic violence were selected as the study sample, employing an accessible sampling technique, and were randomly assigned to either the experimental or control group (20 participants in each group). The experimental group received emotion-focused therapy for a duration of 8 sessions, with each session lasting one hour, over a period of 4 weeks. Conversely, the control group did not receive any form of intervention. The research instrument employed was Maslow's (2004) questionnaire on the perception of psychological security, which was completed by the participants during the pre-test and post-test stages. The collected data was analyzed using SPSS-22 software and covariance analysis. Results: The findings indicated that emotion-focused therapy has a significant impact on the perception of psychological security and its components in women affected by domestic violence. Conclusions: Consequently, this therapeutic approach can be utilized to enhance the well-being of women experiencing domestic violence and thus have beneficial effects on their children' academic and emotional outcomes.